Peace without consensus power sharing politics in Northern Ireland - Clancy, Mary Alice C. (Routledge is an imprint of the Taylor & Francis Group, an informa business, 2010)
1. The formation of Northern Ireland, ethno-nationalism, and consociationalism -- 2. The 'high politics' of the Sunningdale and Anglo-Irish agreements -- 3. An agreed approach? The 'high politics' of the Belfast Agreement -- 4. Saving Dave? The high politics of the post-agreement period, 1998-2000 -- 5. All changed, all changed utterly? September 11th and beyond -- 6. 'You never hit a homerun with these things, sometimes you get a walk' : Northern Ireland, 2004-2007 --7. Conclusion